2018
DOI: 10.7554/elife.32744
|View full text |Cite
|
Sign up to set email alerts
|

Rad52-Rad51 association is essential to protect Rad51 filaments against Srs2, but facultative for filament formation

Abstract: Homology search and strand exchange mediated by Rad51 nucleoprotein filaments are key steps of the homologous recombination process. In budding yeast, Rad52 is the main mediator of Rad51 filament formation, thereby playing an essential role. The current model assumes that Rad51 filament formation requires the interaction between Rad52 and Rad51. However, we report here that Rad52 mutations that disrupt this interaction do not affect γ-ray- or HO endonuclease-induced gene conversion frequencies. In vivo and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
39
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 54 publications
11
39
2
Order By: Relevance
“…We have previously shown that Srs2 removes Rad51 I345T from ssDNA at a reduced velocity (∼85 nt·s −1 ) compared with the velocity observed with WT Rad51 (∼140 nt·s −1 ) (44), indicating that Rad51 I345T slows but does not stop the movement of Srs2, which is consistent with the observed reduction in Srs2mediated ATP hydrolysis in the presence of Rad51 I345T . Together, these findings suggest that Rad55/57 (22), Rad52 (24,42), and Rad51 I345T (present study and ref. 44) do not function by inhibiting Srs2 ATP hydrolysis activity.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…We have previously shown that Srs2 removes Rad51 I345T from ssDNA at a reduced velocity (∼85 nt·s −1 ) compared with the velocity observed with WT Rad51 (∼140 nt·s −1 ) (44), indicating that Rad51 I345T slows but does not stop the movement of Srs2, which is consistent with the observed reduction in Srs2mediated ATP hydrolysis in the presence of Rad51 I345T . Together, these findings suggest that Rad55/57 (22), Rad52 (24,42), and Rad51 I345T (present study and ref. 44) do not function by inhibiting Srs2 ATP hydrolysis activity.…”
Section: Resultssupporting
confidence: 87%
“…Rad55/57 and Rad52 have been implicated as potential regulators of Srs2 activity, albeit through poorly understood mechanisms (21,22). Interestingly, Rad55/57 and Rad52 have no impact on Srs2 ATP hydrolysis rates (22,24,42), and Srs2 readily removes Rad52 from RPA-ssDNA complexes (42). Rad51 I345T is a suppressor mutation that bypasses the need for Rad55/57 (22,43).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rad52 aids this process by mediating the loading of Rad51 onto ssDNA coated with the ssDNA binding protein RPA (Krogh and Symington, 2004). It also helps protect Rad51-ssDNA filaments from disruption by the anti-recombinogenic DNA helicases Srs2 and Fbh1 (Lorenz et al, 2009; Ma et al, 2018; Osman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%